Flexural Behaviour of RC beams using GFRP Composites - Sivasankar, S; Bharathy, T; Vinodh Kumar, R (International Journal of Engineering and Technology, 2018)
Reinforced Concrete (RC) structures damaged by sudden accidental loads due to earthquake and severe environmental exposure. Traditional strengthening methods are not meeting the service life of the structure for long time. Recently, FRP strengthening is used successfully in all kind of exposure with minimum cost and less duration. In this paper RC beams were strengthened by GFRP sheets in two different orientations. Two specimens are control beams, two specimens are wrapped with U wrapping and the remaining beams are bottom wrapping. The size of the beam is 1700mm long, 150mmÂ wide and 250mm depth. The test specimens consit of 2 nos of 10mm dia rods as longitudinal reinforcement in compression zone and 2 nos of 10mm dia steel rods in tension zone. 2-legged stirrups of 8mm diameter were used with a centre-to-centre spcaing of 150mm. All beams were tested under four-point loading. Experiments will be undertaken until beams fails so that the influence of GFRP characteristics on the Flexural behaviour of beams which includes Flexural behaviour, Ultimate load carrying capacity, Deformation and Stress-strain behaviour. Evaluation of the results will lead to optimum GFRP jacketing /wrapping arrangements for the concrete beams are considered here. Â